Morphological variations and phylogenetic analysis of Oryzias nigrimas Kottelat, 1990 (Rice fish) from Lake Poso, Central Sulawesi, Indonesia - NOVALINA SERDIATI; DIANA ARFIATI; MAHENO SRI WIDODO; TRI JOKO LELONO; SAMLIOK NDOBE; RUDY SARANGA (Society for Indonesian Biodiversity, 2020)
Abstract. Serdiati N, Arfiati D, Widodo MS, Lelono TJ, Ndobe S, Saranga R. 2020. Morphological variations and phylogenetic analysis of Oryzias nigrimas Kottelat, 1990 (Rice fish) from Lake Poso, Central Sulawesi, Indonesia. Biodiversitas 21: 882-888. Rice fish (Oryzias nigrimas Kottelat, 1990) is a well-studied species endemic to Lake Poso, Sulawesi and identified as scarce. This study aims to identify the Rice fish of Lake Poso, Central Sulawesi based on morphological characters (15 morphometric characters and 5 meristic counts) and phylogenetic analysis using maximum-likelihood (ML) method based on mtDNA, CO1 gene. Based on the morphological analysis, it was showed that the meristic counts show significantly different only on the lateral line scale. However, the morphometric measurements show significantly different characteristics on postorbital distance, body depth, and length of jaw. Our phylogenetic analysis also showed that our samples are indeed a species of O. nigrimas. We suggest that the endemicity of this Rice fish on Lake Poso is greatly influenced by the well-maintained genetic structure of the population.